2002
DOI: 10.1023/a:1021349304885
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The effects of platelet activating factor (PAF) and its cell analogs 1-O-alk-1;-enyl-2-acetyl-sn-glycero-3-phosphocholine (1-alkenyl-PAF) and 1-acyl-2-acetyl-sn-glycero-3-phosphocholine (1-acyl-PAF) on chemotaxis of human leukocytes in vitro and their inflammatory and antiinflammatory activities in vivo were studied. Both analogs stimulated chemotaxis of human leukocytes in agarose gel. PAF and 1-alkenyl-PAF induced rat paw edema in the range of doses 0.1-10 and 10-100 micro g per paw, respectively. Paw edema … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
20
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(28 citation statements)
references
References 14 publications
8
20
0
Order By: Relevance
“…The principal results were the first observation and characterization of the (2)2, (2)3, (2)5, and (1)6 states in their lowest vibrational level and of new vibrational levels in the (1)5 and (2)4 states (m = 1 and m = 1, 2, respectively). Noting that the energies of the observed low-lying states agree very well with those calculated by Kulikov [4] using ligand field theory, the authors concluded that these states arise from the atomic ion Nd 2+ [4f 3 ( 4 I)6s] configuration which is expected to give 56 states, all predicted to lie below 8000 cm À1 . However, for several states only rough estimates of the parameters could be proposed, and a number of fluorescence patterns remained unexplained.…”
Section: Introductionsupporting
confidence: 63%
See 4 more Smart Citations
“…The principal results were the first observation and characterization of the (2)2, (2)3, (2)5, and (1)6 states in their lowest vibrational level and of new vibrational levels in the (1)5 and (2)4 states (m = 1 and m = 1, 2, respectively). Noting that the energies of the observed low-lying states agree very well with those calculated by Kulikov [4] using ligand field theory, the authors concluded that these states arise from the atomic ion Nd 2+ [4f 3 ( 4 I)6s] configuration which is expected to give 56 states, all predicted to lie below 8000 cm À1 . However, for several states only rough estimates of the parameters could be proposed, and a number of fluorescence patterns remained unexplained.…”
Section: Introductionsupporting
confidence: 63%
“…However, he noticed a splitting of the lines due to X doubling effects in the upper level of the transition, for J > 20 up to J 0 = 29 (the highest level observed in his spectra and also in ours: the regular line pattern breaks off abruptly). The lines reported by Kaledin et al [2] correspond to the upper (a) sublevels identified by Kulikov [4]. We have reanalysed this band and observed the splitting found by Kulikov.…”
Section: The [156]6 à (2)5 System (System V)mentioning
confidence: 51%
See 3 more Smart Citations